Hyperspectral response of cape gooseberry (Physalis peruviana L.) plants inoculated with Fusarium oxysporum f. sp. physali for vascular wilt detection - Giraldo-Betancourt, Cristhian; Velandia-Sánchez, Edisson Andrés; Fischer, Gerhard; Gómez-Caro, Sandra; Martínez, Luís Joel (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2020)
This study used greenhouse conditions to determine the hyperspectral responses of cape gooseberry (Physalis peruviana L.) plants inoculated with different Fusarium oxysporum f. sp. physali densities because the causal agent of vascular wilt generates great economic losses for farmers. A completely randomized design with four replicates was established. The evaluated treatments were inoculum densities 0.0, 1.0·103 and 1.0·106 conidia/mL of the pathogen. The inoculation was done with immersion of roots in conidia suspensions. The spectral response was directly measured on the plant leaves with a spectroradiometer. Non-invasive detection in the P. peruviana - F. oxysporum pathosystem with reflectance values was used with different spectral indices related to the visible and Red Edge, which were calculated and correlated with the disease variables. The treatments showed significant differences in the visible spectrum starting 14 days after inoculation with higher reflectance values. The chlorophyll index at the red edge (ChRE), the modified chlorophyll absorption index (MCARI), the simple ratio index (SR) and the Zarco & Miller index (ZM) showed highly significant correlations with the area under the disease progress curve for leaves (AUDPCL), leaf area and fresh weight of the aerial part of the plants. This study showed the potential of spectral patterns for the detection and study of Fusarium wilt in P. peruviana.